PENGARUH PROFITABILITAS DAN RISIKO KEUANGAN TERHADAP PERATAAN LABA DI ASEAN - Shakila Putri Amanda; Widiastuty, Erna (Jurnal Riset Akuntansi, 2024)
This study examines the effect of profitability and financial risk on income smoothing practices in banking companies listed on the Indonesia Stock Exchange, Singapore Exchange, Bursa Malaysia Securities Berhad, and the Philippine Stock Exchange from 2016 to 2023. Using purposive sampling, 544 firm-year observations were selected. Data were collected from annual reports, company websites, and Datastream Refinitiv Eikon. Multiple linear regression analysis conducted with IBM SPSS Version 25. The results of this study indicate that profitability and financial risk have a negative and significant effect on income smoothing. These findings emphasize the need for considering profitability and financial risk in formulating financial management strategies, aligning with POJK RI Regulation No. 17/PJOK.04/2020. Regulators should consider enhancing disclosure requirements related to values in financial reports.